PERJUANGAN PEREMPUAN DALAM SYAIR NAZIK AL-MALAIKAH PERSPEKTIF FEMINISME EKSISTENSIALIS SIMONE DE BEAUVOIR - Julianingsih, Wiwik (Ihya al-Arabiyah: Jurnal Pendidikan Bahasa dan Sastra Arab, 2026)
This study examines the representation of women's struggle in the poems Ana and Al-Kulira by Nazik al-Malaikah through the perspective of Simone de Beauvoir's existentialist feminism. The research addresses the problem of women's marginalization within patriarchal structures as reflected in modern Arabic poetry. The objective of this study is to reveal how women's existential experiences, resistance, and search for freedom are articulated through poetic symbols and metaphors. This research employs a qualitative library research method using critical textual analysis. The poems are analyzed through close reading and interpreted using key concepts of existentialist feminism, such as the Other, immanence-transcendence, and existential freedom. The findings show that Nazik al-Malaikah portrays women as subjects who experience oppression yet actively struggle to assert their existence. Poetry functions as a medium of resistance and transcendence, enabling women to challenge patriarchal domination and redefine their existential identity.